EFFECTS OF GRAIN SIZE, STRAIN RATE, AND TEMPERATURE ON THE MECHANICAL PROPERTIES OF FENICRCOCU ALLOY USING MOLECULAR DYNAMICS SIMULATION - Hermawan, Kevin
In recent years, high-entropy alloys have become a category of materials that has drawn significant attention from researchers across various fields of materials science. Currently, FeNiCrCo-based alloys have emerged as one of the most extensively studied high-entropy alloy systems due to their highly promising tensile strength and ductility. In this study, Cu was added to the alloy in an equiatomic composition to enhance its radiation and corrosion resistance. The mechanical properties of FeNiCrCoCu alloys are influenced by several key factors, such as grain size, strain rate, and temperature. Molecular dynamics simulation is one of the most effective and efficient tools for studying the mechanical properties of alloys under various grain sizes, strain rates, and temperatures. The molecular dynamics simulation begins with the construction of polycrystalline FeNiCrCoCu samples using the Atomsk software to prepare alloys with different grain size variations (4.8, 6.8, and 9.0 nm). The simulation continues with uniaxial tensile tests conducted using the large scale atomic/molecular massively parallel simulator (LAMMPS) software under varying strain rates (0.001, 0.004, 0.01, and 0.04 ps-1) and temperatures (100, 200, 300, 400, and 500 K). These simulations produce stress-strain curves that can be analyzed further to obtain the values of elastic modulus, yield strength (YS), and ultimate tensile strength (UTS) of the alloy. Additionally, using OVITO software, phase transformations occurring during deformation will be studied through the common neighbor analysis (CNA) feature, while dislocation behavior will be examined using the dislocation analysis (DXA) feature during plastic deformation. The results of the uniaxial tensile test simulation indicate that the strength and ductility of FeNiCrCoCu alloy increases with the increase in grain size, ranging from 4.8 nm, 6.8 nm, to 9.0 nm, with UTS values of 4.70 GPa, 5.12 GPa, and 5.91 GPa, respectively. The CNA results show an increase in the ratio of the HCP phase in larger grain sizes, which correlates with enhanced alloy strength. The DXA results indicate that twinning formation becomes the dominant deformation mechanism in larger grain sizes, which is associated with improved ductility of the alloy. Furthermore, increasing the strain rate from 0.001 ps-1 to 0.04 ps-1 also enhances the alloy’s strength, with UTS values increasing from 4.07 GPa to 6.93 GPa. Meanwhile, increasing the operating temperature from 100 K to 500 K reduces the alloy’s strength, with UTS values decreasing from 5.54 GPa to 4.79 GPa.